The effect of conditioning and natural aeration methods on rate of moisture loss and crude protein content of Lablab purpureus herbage during hay-making. Issue 4 (1st October 2016) - Manyawu, Godfrey; Gwiriri, Lovemore C; Chakoma, Irenie; Moyo, Siboniso; Dube, Sikhalazo
Abstract : The objective of this on-farm study was to develop an effective and labour-extensive method to cure forage Lablab purpureus ' Highworth' for resource-constrained smallholder farmers in the Goromonzi district, Zimbabwe in 2014. In a completely randomised factorial design, the drying rate of forage subjected to three conditioning treatments, viz. pressing with a plain water-filled 200 L steel drum, pressing with a water-filled 200 L steel drum covered with 14-gauge wire mesh, and chopping to 5 cm length with a machete, was compared with that of unconditioned forage. The conditioning treatments were subjected to three natural aeration methods, viz. Aframe, raised platform, and dry ground. Replicated four times, conditioned forage was cured at a swath density of 25 kg m−2 to cover 3 m2 per treatment over 28 d. Conditioning of forage had a significant ( p < 0.05) effect on drying rate. However, conditioning did not have a significant ( p > 0.05) effect on crude protein content. Aeration treatments did not have a significant effect ( p > 0.05) on drying rate or crude protein content. Moisture loss rate was higher for forage conditioned with a wired drum and machete. Conditioning with a machete was most labour intensive compared with drum conditioning treatments. Laceration and pressing is an effective and labour-extensive conditioning method for resource-constrained smallholder farmers.